A Study on New Model of Education System - x. Swati Garg, (AG Volumes, 2022)
In recent years, the educational landscape has heated up to the level of intense competition that formerly existed only among universities. Institutions can only thrive by providing increasingly high-quality products and services. In India, the educational system has been completely revamped thanks to the Right to Education Act. While India's higher education system has several obstacles, there are also numerous openings through which these problems might be solved and the system improved. Better openness and responsibility are required. In this research, we analyse the current state of Indian education and pinpoint new problems and difficulties.An individual's confidence, daring, ability to make sound judgments, and expansion of worldview can all be attributed to the preparation they received in their formative years, which is why education is so important. To guide one toward a life that is both helpful and meaningful is education's fundamental goal. The disparity in educational quality is a major issue in the modern world. Education is often seen as a barometer of a society's economic success. In today's world, having a college degree is almost required for success. The primary goal of this research paper is to gain an understanding of the issues plaguing the Indian education system. The main areas that have been highlighted are the following: the need and significance of education; issues in the Indian education system; challenges facing the Indian education system; and suggestions for improving the Indian education system.